2015
DOI: 10.1111/jdi.12370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a sodium glucose co‐transporter 2 selective inhibitor, ipragliflozin, on the diurnal profile of plasma glucose in patients with type 2 diabetes: A study using continuous glucose monitoring

Abstract: Aims/IntroductionTo assess the effects of sodium glucose co-transporter 2 inhibitor therapy on the pathophysiology of type 2 diabetes.Materials and MethodsWe administered ipragliflozin to 21 inpatients with type 2 diabetes for 7 days, and analyzed the diurnal profiles of plasma glucose and 3-hydroxybutyrate. A total of 21 age-, sex- and body mass index-matched diabetic patients served as controls.ResultsContinuous glucose monitoring showed that the 24-h glucose curve was shifted downward without hypoglycemia b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 29 publications
10
16
0
Order By: Relevance
“…The HOMA‐β values increased and PI/I ratio decreased in the sitagliptin group compared with the ipragliflozin group. Recent reports have shown that 7‐day or 4‐week treatments with ipragliflozin improved β‐cell function, assessed by HOMA‐β and the disposition index during 75‐g oral glucose tolerance test, respectively . In the present study, the HOMA‐β and PI/I ratios were unchanged after 12‐week treatment with ipragliflozin.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The HOMA‐β values increased and PI/I ratio decreased in the sitagliptin group compared with the ipragliflozin group. Recent reports have shown that 7‐day or 4‐week treatments with ipragliflozin improved β‐cell function, assessed by HOMA‐β and the disposition index during 75‐g oral glucose tolerance test, respectively . In the present study, the HOMA‐β and PI/I ratios were unchanged after 12‐week treatment with ipragliflozin.…”
Section: Discussionsupporting
confidence: 93%
“…Recent reports have shown that 7-day or 4-week treatments with ipragliflozin improved β-cell function, assessed by HOMA-β and the disposition index during 75-g oral glucose tolerance test, respectively. 13,14 In the present study, the HOMA-β and PI/I ratios were unchanged instance, sitagliptin might be more beneficial for those with insulin secretory dysfunction and ipragliflozin for those with excessive fat and insulin resistance.…”
Section: Discussionmentioning
confidence: 43%
“…Furthermore, in the Continuous Glucose Monitoring study, luseogliflozin 2.5 mg once daily for 7 days shifted the area under curve (AUC) for glucose to lower levels, and both AUC and peak glucose levels significantly reduced in patients with mildly impaired glycemic control. Similarly, Yamada et al . reported that the ipragliflozin treatment improved the entire 24‐h glucose AUC without causing hypoglycemia.…”
Section: Clinical Usefulness Of Sglt2 Inhibitors In Combination With mentioning
confidence: 84%
“…Furthermore, in the Continuous Glucose Monitoring study 27 , luseogliflozin 2.5 mg once daily for 7 days shifted the area under curve (AUC) for glucose to lower levels, and both AUC and peak glucose levels significantly reduced in patients with mildly impaired glycemic control. Similarly, Yamada et al 28 reported that the ipragliflozin treatment improved the entire 24-h glucose AUC without causing hypoglycemia. Finally, Japanese patients with type 2 diabetes inadequately controlled with sulfonylureas were randomly assigned to receive luseogliflozin 2.5 mg or a placebo for 24 weeks, and the placebo-adjusted mean reduction in HbA1c was -0.88% in the treatment group 29 .…”
Section: Clinical Usefulness Of Sglt2 Inhibitors In Combination With mentioning
confidence: 88%
“…Notably, the reduction in blood glucose distribution width induced by ipragliflozin suggests that ipragliflozin reduces glucose spikes, the difference between maximum plasma glucose and fasting plasma glucose levels. Although Yamada et al ,. reported that ipragliflozin simultaneously lowered preprandial and postprandial glucose excursions in patients whose HbA1c level was higher than that of the present study or in patients treated with hypoglycemia‐inducible antidiabetic medications, the improvements in glucose spikes reported seem to be lower than in the present study.…”
Section: Discussionmentioning
confidence: 99%